The Effect of Lifestyle on Skin Aging - Yasmin Adzra Nabila; Damayanti Damayanti; Samsriyaningsih Handayani; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Skin aging is a natural process, and it has many causes. Skin aging can be a result of a process of deterioration of the skin structure and a decrease in normal skin function. As much as 97% of skin aging factors is extrinsic, while the remaining 3% of the factors is intrinsic. Extrinsic factors are closely related to lifestyle; therefore it is necessary to further investigate the effects of lifestyle on skin aging. Skin aging may not have a direct correlation to mortality but the process of aging itself can lead to depression, demoralization, and shame at the extreme to the point of accepting the changes that occur with age. This shows that aging plays an important role in decreasing the quality of human life and youth well-being index, especially in women. Purpose: To determine the effects of lifestyle on skin aging. Methods: This was a case-control study. A case means a person with heavy aging, and control means an individual with mild aging. The data were obtained from medical records and anamneses. Data on lifestyle were collected through interviews with open-ended questions. Subjects who met the inclusion criteria were shortlisted, and their skins were examined as per the Glogau scale. Result: Multivariate test results showed significant results on the variable UV light exposure (p = 0.017), use of sunscreen (p = 0.002), use of anti-aging cream (p = 0.036), and Vitamin D (p = 0.040) against skin aging. Meanwhile, other variables showed no significant results. Conclusion: Lifestyle has an important role in the occurrence of skin aging. However, an in-depth research is needed to determine how many external factors affect skin aging.